Systemic autoimmune diseases and work outcomes in Brazil: a scoping review - Cordeiro, Rafael Alves; Fischer, Frida Marina; Shinjo, Samuel Katsuyuki (Revista de Saúde Pública, 2022)
OBJECTIVE To review articles that assessed work-related outcomes such as workability, work productivity, presenteeism, absenteeism, sick leave, return to work, and employment status of Brazilian patients with rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, Sjögren’s syndrome, and systemic autoimmune myopathies. METHODS This study was conducted in Medline databases (PubMed), SciELO, and Lilacs through a combination of descriptors of interest. Studies published until December 2020 were considered in the search strategy. RESULTS Eight out of 90 articles met the eligibility criteria and were included in this review. The studies are highly heterogeneous. Most of them are cross-sectional, and all of them address rheumatoid arthritis or systemic lupus erythematosus. A common denominator among these studies is the high proportion of patients outside the labor market. CONCLUSIONS In general, the studies show unfavorable labor outcomes and impaired participation in the Brazilian workforce among the samples of patients assessed. There is a need to better understand several topics about Brazilian patients with systemic autoimmune diseases and their work context, as well as to conduct studies focusing on rarer diseases and on the themes of return and reintegration to work.